WIĘŹ RODZINNA A MEDIA ELEKTRONICZNE - Dyczewski, Leon (Wydział Prawa i Administracji UAM, 2005)
The analysis of mutual relations between family bonds and electronic media allows the formulation of the following statements: 1. Electronic media can play either a positive or a negative role in relation to the family bond. This depends on the kind of medium, kind of family bond, and the media competence of the generations and particular family members. Generally media fulfil a more positive role in relation to the structural-objective bond in the family than in relation to the personal and cultural bond. This latter one is rather negatively influenced, as the youngest generation adopts from the media certain values, norms and behaviour patterns that are different from those maintained by the family, and if there is no dialogue on this topic in the family, generations may differ widely from each other. It is easy, then, to imagine a situation in which representatives of three generations go in the newest car model bought through the Internet and they are silent because they accept disparate systems of values and norms, behaviour patterns, ideas of life and likings. 2. Electronic media (especially television and the Internet) and the family should not be looked on as contradictory but rather complimentary institutions. It is in this direction that legislature and media education should go. This is also how they should be viewed by decision-makers in the world of television and the Internet, by authors of television programs and websites, as well as by their very recipients. 3. The most important factor that determines the positive or negative effect of media on the family bond is the parents’ and the children’s media competence. With the present development of the media this competence should be developed from early childhood in the family, and then at school from its first to last level. In an attempt to eliminate, or at least weaken, the negative effects of electronic media on the family bond, several actions should be taken. Here are some suggestions that seem to be both important and feasible: a. Actions taken by the family; b. Actions undertaken by the education system; c. Actions undertaken by the family and the media policy; d. Actions undertaken by the broadcasters; e. Actions undertaken by organizations protecting TV-viewers; f. Actions undertaken by religious groups, first of all by the Catholic Church in Poland. Electronic media are an invention that is too new and has too many tasks to comprehensively and positively integrate with the family life. They have most positively integrated with the structural- objective family bond. One may hope that in the nearest future a better integration of electronic media with the personal bond will take place. However, an integration of electronic media with the cultural family bond will be the most difficult.
FAMILY BONDS VS ELECTRONIC MEDIA